2021
DOI: 10.5334/cstp.341
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Citizen Science Program Participation and the Role of the Organization: Lessons from Water Quality Monitors in Texas

Abstract: Citizen science (CS) programs often question what motivates their volunteers and how volunteer participation can be sustained. Using a case study of citizen scientist volunteers (CSVs) who monitor water quality in Texas, I apply here a novel approach-the Dispositional-Organizational Interactions Framework (DOIF)-that provides a nuanced understanding of CSVs. The DOIF allows for consideration of how dispositional variables, such as sociodemographic characteristics and motivations for participation, may relate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
1
7
1
Order By: Relevance
“…In their communication, projects could, for example, highlight the link to the participants' everyday life, which appears to be a strong motivator in our as well as in other studies (Wagenknecht et al, 2021). In contrast, we did not find that contributing to science and learning about science were powerful recruitment messages or motivators, which is counter to a number of other studies (Raddick et al, 2010;Curtis, 2015;Land-Zandstra et al, 2015;Alender, 2016;Land-Zandstra et al, 2016;Lee et al, 2018;Lopez, 2021;Etter et al, 2023). Community building through science communication among participants as well as between participants and scientists has also been described as a success factor for CS projects (Golumbic et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…In their communication, projects could, for example, highlight the link to the participants' everyday life, which appears to be a strong motivator in our as well as in other studies (Wagenknecht et al, 2021). In contrast, we did not find that contributing to science and learning about science were powerful recruitment messages or motivators, which is counter to a number of other studies (Raddick et al, 2010;Curtis, 2015;Land-Zandstra et al, 2015;Alender, 2016;Land-Zandstra et al, 2016;Lee et al, 2018;Lopez, 2021;Etter et al, 2023). Community building through science communication among participants as well as between participants and scientists has also been described as a success factor for CS projects (Golumbic et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The ENPO community partner is headquartered in San Marcos, Texas, USA, but operates throughout the state of Texas with over 25 partner organisations. They have many stewardship programs, but the focal program for this research was water quality monitoring through citizen science (Lopez 2021). The ENPO has trained over 10,000 volunteers to monitor surface water across Texas, and approximately 400 of those volunteers monitor on a recurring, monthly basis.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, extrinsic motivators are subdivided into: 1) the perceived balance and direct costs and benefits of natural resource protection (Lopes and Videira 2013;Gandiwa et al 2013); and 2) externally provided social, physical, economic or legal rewards (Bennett et al 2018). Multiple studies suggest that intrinsic motivations are predominant in ES (Bramston, Pretty and Zammit 2011;Lopez 2021;Lopez and Weaver 2021), insofar as they might be more durable and longer lasting than extrinsic motivations (Bennett et al 2018: 603). Moreover, previous studies that seek to understand volunteer motivations have found that helping the environment (an intrinsic motivator) is typically the most frequently selected reason, whereas career advancement (an extrinsic motivator) is the least frequent selection (Grese et al 2001;Bruyere and Rappe 2007;Alender 2016).…”
Section: Environmental Valuesmentioning
confidence: 99%
“…social and career in VFI) [ 34 ]. On the other hand, a study examining variations in VFI across different participation durations in a water quality monitoring program found that the ‘career’ function positively influenced sustained engagement for specific demographics, including nonwhite individuals, college students, lower-income earners, those employed in the environmental sector, and younger participants [ 35 ]. These findings emphasize the importance of aligning project objectives with participants’ values and interests, while also recognizing the influence of socio-economic and cultural factors on sustained engagement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%